2017
DOI: 10.1039/c6fd00239k
|View full text |Cite
|
Sign up to set email alerts
|

Is an electric field always a promoter of wetting? Electro-dewetting of metals by electrolytes probed by in situ X-ray nanotomography

Abstract: We developed a special electrochemical cell enabling quantitative analysis and in situ X-ray nanotomography of metal/electrolyte interfaces subject to corrosion. Using this cell and applying the nodoid model to describe menisci formed on tungsten wires during anodization, the evolution of the electrolyte surface tension, the concentration of reaction products, and the meniscus contact angle were studied. In contrast to the electrowetting effect, where the applied electric field decreases the contact angle of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Since most materials are hydrophilic, a dewetting actuation, if found to be effective, would enable digital microfluidics just as EWOD does, but without the requirement for the hydrophobic coating. Although most electrically induced dewetting phenomena are not effective for common microfluidics because they are based on irreversible processes 17,18 or special conditions 19 , studies involving surfactants have shown that reversibility may be possible. For example, electrically initiated dewetting of an aqueous film on derivatized gold electrodes has been demonstrated using redox-active surfactants 20 .…”
mentioning
confidence: 99%
“…Since most materials are hydrophilic, a dewetting actuation, if found to be effective, would enable digital microfluidics just as EWOD does, but without the requirement for the hydrophobic coating. Although most electrically induced dewetting phenomena are not effective for common microfluidics because they are based on irreversible processes 17,18 or special conditions 19 , studies involving surfactants have shown that reversibility may be possible. For example, electrically initiated dewetting of an aqueous film on derivatized gold electrodes has been demonstrated using redox-active surfactants 20 .…”
mentioning
confidence: 99%